Effect of Date of Transplanting, Spacing and Training System on Quality Characters of Tomato (Solanum lycopersicum Mill) Under Naturally Ventilated Polyhouse - Kaushal, S.; Sharma, V. (Indian Journal of Hill Farming, 2018)
An experiment was conducted in naturally ventilated polyhouse during summer-season (March to August) in the year 2013 and 2014 at the Research Farm of the Himachal Pradesh Krishi Vishvavidyalaya, Palampur, to study the effect of date of transplanting, spacing and training system on quality characters of tomato (Solanum lycopersicum Mill) under naturally ventilated poyhouse. The experiment was laid out in randomized block design with three replications, consisting of twelve treatments i.e. three dates of transplanting (15th March , 30th March and 15th April), two spacings (60 cm x 30cm and 75 cm x 30 cm) and two training systems (two shoots and three shoots). Plants transplanted on 15th March recorded significantly higher pericarp thickness (7.1 cm in 2013 and 7.5 cm in 2014), maximum TSS (5.33% in 2013 and 5.50% in 2014), higher ascorbic acid (24.4 mg/100g in 2013 and 22.7 mg/100g in 2014), maximum titrable acidity (0.50% in 2013 and 0.51% in 2014). It was observed that plant spacing of 75 cm x 30 cm resulted in higher pericarp thickness (7.1 cm in 2013 and 7.3 cm in 2014), maximum TSS (4.83% in 2013 and 5.11% in 2014), maximum titrable acidity (0.44% in 2013 and 0.46% in 2014) except ascorbic acid which was recorded higher in 60 cm x 30 cm spacing whereas, training plant to two shoots recorded significantly higher pericarp thickness (6.9 cm in 2013 and 7.2 cm in 2014) other characters were not affected significantly with different treatments.